Design of thin circuit‐analogue multilayer absorber and application to leading edge of wing structure. Issue 3 (1st January 2013) - Choi, W.H.; Shin, J.H.; Song, T.H.; Kim, J.B.; Lee, W.J.; Joo, Y.S.; Kim, C.‐G.
Abstract : A new thin multilayer circuit‐analogue (CA) absorber design consisting of a patterned resistive sheet, glass/epoxy, and glass/MWCNT‐epoxy for X‐band radar is presented. The proposed thin multilayer CA‐absorber (a total thickness of 2.23 mm) has smaller thickness by 0.71 mm than a single‐layer CA‐absorber (a total thickness of 2.93 mm). Although the absorption bandwidth of the multilayer CA‐absorber in the X‐band was slightly narrower than the single‐layer CA‐absorber, the absorption performance of the multilayer CA‐absorber was comparable to that of the single layer. Also, when the CA‐absorber was applied to the leading edge of a wing‐shaped structure, the radar cross‐section level was comparable with the single‐layer CA‐absorber even though the thickness of the multilayer CA‐absorber was less than that of the single‐layer CA‐absorber.